Return Reversal Anomaly: Contrarian and Risk Adjusted Multifactor Examination of BSE Index Marriam Rao - Rao , Marriam; Qamar, Muhammad Ali Jibran; Siddiqui, Ahmad Faisal (International Journal of Psychosocial Rehabilitation, 2020)
Study of factors generating return reversal anomaly in emerging market is inconclusive and controversial. This study examines existence and risk adjusted multiple factors originating reversal profits in the short and long run in Bombay Stock Exchange (BSE), India biggest stock market on monthly bases from January, 2005 till December, 2019. Reversal profit existence are studied in short/long run via building (8*8=64) portfolios with formation period of J=1,3,6,12,24,36,48,60 month and holding period of K=1,3,6,12,24,36,48,60 months. Amongst 64, 23 reversal combination portfolios generated profitable excess returns where winner becomes loser and loser becomes winner portfolio. The highest and significant reversal profits are indicated with formation period of J= 60 months and holding period of K= 60 months indicating BSE Index to revert with profitable returns in a time span of 5 years. Further risk adjusted factors originating reversal effect in BSE market are examined via application of median based Quantile regression models. The study contributes with inclusion of volatailty and long term reversal factor in Fama & French five factor model. Results demonstrate volatailty and long-term reversal produce significant results depicting multi factor model to be more powerful and appropriate to reason for return reversal anomaly.